Modification of lignin content in wood fiber by microwave heating and laccase treatment - Muhammad 'Izzat, Saidon (2010)
Oxidoreductases and by microwave heating can be applied for bonding of fiberboards. The objectives of this research are to modify the lignin content of wood fibers by using enzymatic treatments and by microwave heating treatments to make binderless boards and to determine the use of laccase treatment and by microwave heating can give promise and possibilities for industrial bonding and modification of lignin. In this research, the fiberboards were prepared from four different treatments which are untreated, UF-resin treated, microwave heating treated and laccase treated 6U/g fiber boards. Hot pressing at constant 200°C and 4 minutes pressing was done to form the boards. For each treatment the boards were tested for modulus of elasticity (MOE), modulus of rupture (MOR) and internal bond strength (IB). From the results obtained, the microwave heating treated boards displayed quite comparable in average mechanical property within the UF-resin treated (standard) boards meanwhile for laccase treatment of fibers, it displayed the lowest MOR and MOE values. As a conclusion, the microwave heating treatment shows promise and possibilities for industrial bonding and modification of lignin content in wood fiber. However, the laccase treatment can be potentially improved through extensively studies in future regarding on the use of laccase for adhesion enhancement in binderless wood boards because it had been proved on recent studies that laccase used resulting in boards with good mechanical properties without toxic synthetic adhesives. For recommendation, in future, research regarding wood modification in lignin content by microwave heating and enzyme treatment could be optimized and enhance by variances of a number of process parameters such as temperature, time pressing, pressure and moisture content